Does Wage Theft Vary by Demographic Group? Evidence from Minimum Wage Increases - Jeffrey Clemens; Michael R. Strain (Institute of Labor Economics (IZA), 2023)
Using Current Population Survey data, we assess whether and to what extent the burden of "wage theft" - wage payments below the statutory minimum wage - falls disproportionately on various demographic groups following minimum wage increases. For most racial and ethnic groups at most ages we find that underpayment rises similarly as a fraction of realized wage gains in the wake of minimum wage increases. We also present evidence that the burden of underpayment falls disproportionately on relatively young African American workers and that underpayment increases more for Hispanic workers among the full working-age population.
Keywords: J08; J38; K42; 330; minimum wage; subminimum wage; compliance; noncompliance; enforcement; underpayment